Augmented Reality Based Student Worksheets to Improve Understanding of 3D-Shapes Concepts for Fifth Grade of Elementary Schools - Utama, Ketut Gde Sunu; Margunayasa, I Gede (Universitas Pendidikan Ganesha, 2024)
The problem of students who have difficulty understanding the concept of building a space in mathematics lessons. Students tend to find it difficult to understand the material because there is no learning medium that suits the characteristics of students. The research aims to develop an augmented reality-based LKPD on the understanding of the concept of building a classroom for grade V students in elementary school. This development study uses the ADDIE model, namely analysis, design, development, implementation, and evaluation. This study takes the subject of augmented reality-based LKPD, while the object of development research is the validity of media content, material content, practicality of use, and media effectiveness. The data collection method is by rating scale and test. The instruments used to collect data are rating scale sheets, and test sheets. The results of the study showed that the augmented reality-based LKPD obtained a high validity qualification index, the material in the content of the augmented reality-based LKPD media that had been produced obtained a high validity qualification index, the level of achievement of practitioner/teacher response received very good qualifications, the level of achievement of students' response to augmented reality-based LKPD media obtained very good qualifications, and the significance value on the correlated t-test obtained a score by 0.000 < 0.05, so that augmented reality-based LKPD media is effective in increasing the understanding of the concept of building a classroom for grade V students in elementary schools.